(untitled) (Ameghiniana, 2014)
Predation by the gastropod Acanthina is described by means of aquaria observations on living specimens.Results show that Acanthina preys upon the bivalves Mytilus chilensis Hupé, Perumytilus purpuratus (Lamarck), Aulacomya atra (Molina) and the bamacle Chthamalus scabrosus (Darwin). The predator exhibits two methods of attack on captured bivalve prey. It most frequently uses the labral spine to open the shells, leaving irregular marks on the valves of their preys. But, similarly to other muricids, the predator is able to drill cylindrical holes on the shells. These two strategies are compared with those used by other dogwhelks and invertebrates and must be related to the predator fitness.